2017
DOI: 10.1111/eos.12346
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between universal adhesives and two‐step self‐etch adhesives in terms of dentin bond fatigue durability in self‐etch mode

Abstract: This aim of this study was to compare universal adhesives and two-step self-etch adhesives in terms of dentin bond fatigue durability in self-etch mode. Three universal adhesives - Clearfil Universal, G-Premio Bond, and Scotchbond Universal Adhesive - and three-two-step self-etch adhesives - Clearfil SE Bond, Clearfil SE Bond 2, and OptiBond XTR - were used. The initial shear bond strength and shear fatigue strength of resin composite bonded to adhesive on dentin in self-etch mode were determined. Scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 37 publications
(46 reference statements)
5
35
0
1
Order By: Relevance
“…Subsequently, the specimens were stored in 37°C distilled water for 24 h prior to testing. The fatigue load was applied on the stainless‐steel molds using a sine wave at a frequency of 20 Hz for 50,000 cycles or until failure occurred, following the standard methodology for this test . The initial peak load for bond fatigue‐strength testing for each of the adhesives was set at a level of approximately half of the initial bond strength for each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the specimens were stored in 37°C distilled water for 24 h prior to testing. The fatigue load was applied on the stainless‐steel molds using a sine wave at a frequency of 20 Hz for 50,000 cycles or until failure occurred, following the standard methodology for this test . The initial peak load for bond fatigue‐strength testing for each of the adhesives was set at a level of approximately half of the initial bond strength for each group.…”
Section: Methodsmentioning
confidence: 99%
“…Other manufacturers later released similar universal adhesives with various distinctive characteristics, such as use with resin luting cement , use with various substrates , or shortened application times . It has also been reported that the bond durability of most universal adhesives to enamel in etch‐and‐rinse and self‐etch modes and to dentin in self‐etch mode is lower than that of two‐step self‐etch adhesives. Nevertheless, the clinical use of universal adhesives is increasing rapidly because of their versatility.…”
mentioning
confidence: 99%
“…Over the past decade, a dynamic bond strength testing that assess the bond fatigue strength of adhesive systems have been developed at the Creighton University School of Dentistry (Omaha, NE, USA) [28][29][30] . A method for dynamic bond strength testing was originally developed by Erickson et al 31,32) 33) , Barkmeier et al 34) , Takamizawa et al 35) , and Tsujimoto et al 36) at the Creighton University School of Dentistry from 2009 to 2017.…”
Section: Introductionmentioning
confidence: 99%
“…34 The visualization of the type of failure of the tensile bond strength test was performed by a single operator by means of a microscope at 32×, and the failure was classified as cohesive, adhesive, or mixed. 29,33,35 One additional specimen from each group was used for the surface characterization of the different treatment types by means of scanning electron microscopy (SEM) (JSM 6010LA; JEOL, Tokyo, Japan). The images were registered at 300×, 2000×, and 10,000× magnifications for qualitative verification of the surface treatment.…”
Section: Methodsmentioning
confidence: 99%